Women’s Religious Authority in Islamic Education: Sitti Raihanun’s Leadership in Indonesia - Husnul Haetami; Adi Fadli; Abdul Mujib (Women, Education, and Social Welfare, 2026)
This study examines women’s religious authority in Islamic education through the leadership of Hajjah Sitti Raihanun Zainuddin Abdul Madjid and her contribution to educational transformation in Indonesia. Using qualitative library research with historical and sociological approaches, the study analyzes books, journal articles, biographies, organizational documents, institutional archives, and leadership records related to Nahdlatul Wathan. Data were examined through content analysis and interpretative-descriptive techniques. The findings show that Raihanun’s authority was constructed through genealogical legitimacy, personal charisma, leadership competence, religious credibility, and social recognition. Her leadership reflected transformational characteristics, including visionary orientation, consultative decision-making, organizational consolidation, institutional development, and commitment to Islamic educational values. During her leadership between 1998 and 2015, approximately 280 educational institutions, including madrasahs, schools, and Islamic boarding schools, were established or developed across Indonesia. She also founded the Syaikh Zainuddin NW Islamic Boarding School in Anjani, East Lombok, a major woman-led Islamic educational institution. Despite patriarchal resistance, internal organizational conflict, and governance constraints, her leadership strengthened educational networks and expanded women’s participation in religious and educational leadership. This study highlights women’s authority as a negotiated, performance-based, and institutionally sustained form of leadership in contemporary Islamic education.